PENGARUH CURRENT RATIO, DEBT TO EQUITY RASIO, RETURN ON ASSETS, AND FIRM SIZE TERHADAP FIRM VALUE MANUFAKTUR - Evan Gorase; Jamaludin Iskak (Jurnal Paradigma Akuntansi, 2023)
This study aims to understand how Firm Value influenced by Current Ratio, Debt to Equity Ratio, Return on Assets, and Firm Size to Firm Value (PBV) to manufactured company that listed on the Indonesia Stock Exchange on 2018-2020 period. Data were obtained by using multiple regression model and E-views 12 software with manufactured company in Indonesia as an object. To get a valid result, purposive sampling was used as sampling technique and get 69 company as main sample and approached by using multiple linear regression analysis & statistic descriptive. Result shows that Current Ratio has a significant influence on firm value. Despite the fact, T-test also shows that debt to equity ratio, return on asset and firm size has no significant influence on firm value.